A new dimensional measure of antisocial behaviour evaluation (ASBE). Issue 2 (4th March 2021) - Esposito, Concetta; Affuso, Gaetana; Miranda, Maria Concetta; Bacchini, Dario
ABSTRACT: Adolescent thinking about the wrongness of antisocial behaviours plays a key role in their own engagement in antisocial conducts. Nevertheless, measures assessing adolescent antisocial evaluations are not common in literature. Informed by the social domain theory and using adolescent actual thinking about antisocial behaviours, this study developed and validated a new dimensional scale of antisocial behaviour evaluation (ASBE) with two sub-samples of Italian adolescents (Total N = 678; M age = 15.48, SD = 1.61; 291 males). Applying the exploratory factor analysis within the confirmatory factor analysis framework (abbreviated, E/CFA), we found four correlated dimensions of ASBE: The impersonal dimension, including violations carried out against social and legal norms, without any direct contact with other people; the interpersonal dimension, reflecting violations that imply harming other persons; the personal-risky dimension, containing items that refer to violations whose consequences primarily affect one's own safety and health; the loyalty dimension, representing violations that concern reciprocity and loyalty among peers and friends. The scale showed a good internal consistency and validity. The results support a promising use of this new measure for assessing adolescent antisocial thinking and investigating its associations with social cognition, moral reasoning and behaviour.